2002
DOI: 10.1084/jem.20012066
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Expression of Human Histocompatibility Leukocyte Antigen (HLA)-DO During Antigen-dependent and Antigen-independent Phases of B Cell Development

Abstract: Human histocompatibility leukocyte antigen (HLA)-DO, a lysosomal resident major histocompatibility complex class II molecule expressed in B cells, has previously been shown to be a negative regulator of HLA-DM peptide loading function. We analyze the expression of DO in human peripheral blood, lymph node, tonsil, and bone marrow to determine if DO expression is modulated in the physiological setting. B cells, but not monocytes or monocyte-derived dendritic cells, are observed to express this protein. Precleari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
118
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(136 citation statements)
references
References 46 publications
15
118
2
Order By: Relevance
“…These data show that, upon Ag encounter, H2-O −/− B cells have an advantage in entering the GC; however, once they have entered, H2-O −/− and WT B cells have a similar ability to contribute to the expanding GC B-cell pool. This is consistent with data showing that H2-O is down-regulated in WT GC B cells, making them functionally more similar to H2-O −/− B cells (22)(23)(24).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data show that, upon Ag encounter, H2-O −/− B cells have an advantage in entering the GC; however, once they have entered, H2-O −/− and WT B cells have a similar ability to contribute to the expanding GC B-cell pool. This is consistent with data showing that H2-O is down-regulated in WT GC B cells, making them functionally more similar to H2-O −/− B cells (22)(23)(24).…”
Section: Discussionsupporting
confidence: 92%
“…This suggests an important immunological function for H2-O in which H2-O establishes a higher threshold of Ag presentation for cells to commence the GC reaction. Down-regulation of H2-O upon GC entry allows Ag presentation to proceed more efficiently after the entry checkpoint has been passed (22)(23)(24). The GC reaction, albeit a vital part of the immune response, is also inherently dangerous because it combines the active mutagenic mechanisms of somatic hypermutation with rapid cellular proliferation (27).…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that both TgMed and TgHi bmDCs had substantial pools of free H-2M (ϳ90% and ϳ40%, respectively). In human primary B cells and B cell lines, ϳ50 -70% of cellular DM is complexed with DO (5,15,37). Thus, the fraction of H-2M molecules that are DO-associated in DO Tg DCs is similar to that in human B cells.…”
Section: Do Expressing Bmdcs Have Two Pools Of H-2mmentioning
confidence: 89%
“…However, recent studies have suggested that the function of DO may be more multifaceted (9,10). Depending on both the experimental system and the Ag studied, it has been shown that DO can inhibit (7,(11)(12)(13)(14)(15), promote (9,10,16), or have no effect (9,10,12) on class II-peptide loading. Collectively, these studies suggest that DO modifies the loading of specific peptides on to class II molecules, which results in a change in the class II-peptide repertoire (13).…”
mentioning
confidence: 99%
“…in monocytes (4,12). The decrease in relative CLIP/class II levels seen following GM-CSF treatment may reflect a change in DM, Ii, and/or DO expression, and this was tested directly.…”
Section: Gm-csf Increases Total Protein Levels Of Dr Dm II and Do␣mentioning
confidence: 99%